(untitled) (Cadernos de Sociomuseologia, 2023)
The present work aims to discuss the theme of women and their representation in the museological context, especially with regard to university art museums, of which we highlight three to guide our reflection: MusA (UFPR), MUnA (UFU) and MALG (UFPel). Initially, we focus on reflections that deal with women artists from the perspective of their constant invisibilization in the history of museum institutions. We then delve into the panorama of the formal teaching of museology as a discipline in Brazil, from the museum to the university context, highlighting the constitutive presence of women in its theoretical and historical corpus. And finally, by highlighting the panorama of museology and university museums in their specificity, we finally reach our dominant focus in the present study, by carrying out a survey of strategies and actions developed in the Brazilian context that give visibility to the extensive and powerful production of women artists in the institutional profile of the three museums listed for analysis. In addition to presenting the aforementioned initiatives, we consider their implications for the necessary constitution of women’s protagonism, both in the field of museology and in the field of art, in practical, theoretical and poetic actions, as agents of their own experiences and demands, in a dissident and continuous movement that we aim to contribute to. KeyWords: University Art Museums; Women Artists; Brazilian Museology; Social Museology; Gender.